Sustainable natural resource management in the Himalayan Region : livelihood and climate change - Bajracharya, Roshan M.; Sitaula, Bishal K.; Gurung, Smriti; Raut, Nani (2021)
"The greater Himalayan region, stretching from Afghanistan in the west to Myanmar in the east, is home to about a quarter of a billion people who greatly depend on available natural resources for their survival and livelihoods. The ever-increasing population pressure and changing climate have grave implications for the sustenance of human health and habitation in the foreseeable future. The region is confronted with numerous challenges related to forest degradation, land productivity, disaster risk, water management, biodiversity loss, erratic climatic patterns, as well as socio-political capacity. The limits of arable land have essentially been reached, while the need for enhancing production to sustain human nutritive requirements and livelihoods continues to increase. Hence, the intensification of agriculture has become a necessity rather than a choice. Yet, producing greater numbers of crops and quantities of food, fiber and other materials on the same parcel of land runs the risk of degrading the soil fertility, productivity and overall quality. Therefore, means to achieve this without irreversibly damaging the soil and land resource base have become imperative. To this end, agro-forestry, agro-slivi-pastoral systems, and the adoption of a variety of regenerative crops, soil and water management and conservation practices offer the potential to deliver multiple benefits without sacrificing the very resource upon which the human population depends. The need for ecologically sound and sustainable management of natural resources in the Himalayan region, as well as the adaptation of local communities to the impacts of climate change and measures for its mitigation, cannot be over-emphasized. This book presents findings on approaches to sustainable land management and the intensification of agriculture and animal husbandry related to soil organic matter management and carbon sequestration for multiple benefits; and the agroforestry as a crop diversification strategy with livelihood and climate mitigation/adaptation benefits, along with other aspects of forest, biodiversity and water resources management. The book deals with technical, socio-economic, policy and biodiversity issues related to the sustainable use and management of natural resources, namely forests, soil/land, water, crops, animal husbandry and diversity of flora/fauna, as well as disaster risk and vulnerability of communities in the Himalayan region. There is a continuing need to study and research approaches for harmonizing human needs and lifestyles with natural ecosystems and processes so that both may co-exist in a mutually beneficial manner"--
Forest resources management in the context of climate change -- Community-based natural resource management in Nepal / Krishna R Tiwari, Ridish K. Pokharel, Santosh Rayamajhi and Bijendra Basnyat -- Estimation of carbon stocks in Bhutanese forests / Bhagat Suberi -- Diversified agroforestry systems for livelihood security, sustainability and climate resilience of smallholder farms in the Himalaya / Deepak K. Gautam and Roshan M. Bajracharya -- Mountain farming system and soil management -- Regenerative approach for sustainability and climate resilience of mountain agro-ecosystems / Roshan M. Bajracharya -- Agricultural change for rural transformation in Nepal / Nani Raut, Bishal K. Sitaula and Roshan M. Bajracharya -- Soil quality and organic carbon management in a mountainous landscape of the HKH Region in Pakistan / Farida Begum, Roshan M. Bajracharya and Bishal K. Sitaula -- Sustainable land management practices in Bhutan / Tulsi Gurung -- Biochar as a catalyst to enhance productivity of coffee agroforestry systems and local livelihoods in the mid-hills of Nepal / Ngamindra Dahal and Roshan Man Bajracharya -- Natural disaters, resilience and transforming thinking -- Disaster risk reduction and management for resilient mountain communities in Nepal / Chandani Bhandari, Ranjan Kumar Dahal, Manita Timilsina, Kumud Raj Kafle, Gangalal Tuladhar -- Human mindset, attitudes, and behavior influencing natural resource management : water quality in Pakistan / Zoya Arshad and Bishal K. Sitaula -- Vulnerability of local communities to climate-related disasters in the Himalayan Region / Yogeeta Dahal -- Water quality, security and resource management -- Irrigation water quality of Surkhet Valley, Nepal / Smriti Gurung, Nani Raut, Archana Niraula, Jhuna Kattel, Bed Mani Dahal, Pratiksha Koirala, Kumar Khatri, Bibhuti Ranjan Jha and K.C. Sneha -- Water resource management in Bhutan / Ugyen Dorji -- Assessment of water resources with reference to mountain aquifers and spring hydrology in Bhutan / Jambay Jambay -- River water pollution due to vehicle washing in Bhutan / Reeta Rai -- Biodiversity and its conservation -- Spiritual ecology of water : water and prayer in Christianity, Islam, Veda and Avesta / Bishal K. Sitaula, Zoya Arshad and Hugh van Skyhawk -- Status and role of tributaries in fish conservation : fish diversity in Nepalese rivers / Bibhuti Ranjan Jha -- Diatom studies in high altitude lakes in the Himalaya / Ingrid Jüttner, Smriti Gurung, Anu Gurung, Chhatra Mani Sharma and Subodh Sharma -- Knowledge and public perception toward conservation of bats in Bhutan / Sangay Tshering -- Trophy hunting of wild ungulates in northern Pakistan / Muhammad Zafar Khan and Mehmood Ghaznavi -- Policies and governance in natural resources management -- Natural resource management policies and governance in Nepal / Ridish K. Pokharel, Krishna R. Tiwari, Bijendra Basnyat, Santosh Rayamajhi and Bishnu P. Devkota -- Political ecology of environmental conservation : a case of the Bhutan Himalaya / Om Katel and Dietrich Schmidt-Vogt -- Epilogue -- Concluding remarks and future research priorities / Roshan M. Barjracharya, Bishal K. Sitaula, Nani Raut and Smriti Gurung -- About the Editors -- Index.
Includes bibliographical references and index.
Keywords: Natural resources -- Himalaya Mountains Region -- Management; Sustainable development -- Himalaya Mountains Region; Sustainable agriculture -- Himalaya Mountains Region; Climate change mitigation -- Himalaya Mountains Region